to enroll in courses, follow best educators, interact with the community and track your progress.
Enroll
312
3,594 plays

More
This lesson starts with the basic fundamentals of quadratic equation. The standard form of the equation is explained here. The lesson gives the basic method of solving the questions.

Abhishek Kumar
Love to explore life| UPSC Aspirant| Cleared SBI PO| Cleared BOB PO| NDA, AFCAT exam| Attended SSB thrice| Worked as Software engineer IBM

U
IM
Sir only 7day left can I join.
This is a very good introduction to the concept. It's good to refresh and reinforce concepts once in a while. Cheers!
1. Quadratic equation (Basics) Presented by: Abhishek Kumar

2. About me: Cleared Bank Of Baroda PO Cleared SSC CHSL Cracked NDA,AFCAT exam Attended SSB thrice Currently working in IBM India Follow me: https://unacademy.com/userlAbhishek_kr Contribute

3. General form of a Quadratic Equation ax2 + bx + c = 0 Quadratic equation means that it will definitely have the maximum power of the variable as '2" which means we will always see ax2 term in a quadratic equation. Or we can say that b can be 0, c can be 0 but a will never be 0

4. Methods Of Solving quadratic equation >Middle term Splitting > By formula

5. Middle term Splitting Example: 2x2 +11x + 9 = 0 Solution: 2x2 +2x + 9x + 9 = 0 2x(x+1 ) +9(x+1) = 0 (x+ 1 )(2x+9)=0 x =-9/2-4.5 and x =-1

6. By use of formula Example: 4x2 +7x-2 = 0 Solution: 4x2 +7x -2 Example: 4x2+7x -2 acy]/2a x-(-7 M72-4*4*-2)]/24 x=[-7 978 x=-16/2 and x=2/8 x--2 and 0.25 x=(-7-9)/8 and x=(--749)/8 x--2 and

7. Actual question asked in exam Q) I" x2-5x + 6 = 0 Il. y2ty - 6 0 Solution: Solving equation I: x2-5x6 0 x(x-3)-2(x-3) = 0 x2-3x-2x + (3*2) = 0 (x-3)(x-2) = 0 x 2 and 3 Solving equation I: y2 ty-6-0 y2 +3y-2y-6 = 0 y (y+3)-2(y+3) = 0(y+3)(y-2)=0 y -3and 2

8. -3 2 3 We can clearly see using number line that x is greater than y but x and y have a common point. So the relationship between x and y will be x2y.

9. Like, Rate, Review, Recommend

10. Thank you